Internet resources and capabilities: Japanese SME risk-taking, industry and performance. Issue 5 (20th October 2018) - Mathews, Shane W.; Maruyama, Masahiro; Sakurai, Yuka; Bebenroth, Ralf; Luck, Edwina; Chen, Hsiu-Li; Franco, Edward
ABSTRACT: This study investigates how Internet-related resources and capabilities are influencing performance in Japanese small- and medium-sized enterprises (SMEs). We use a structural equation modelling approach to test these relationships between Internet readiness, Internet capability, risk-taking perceptions and performance within Japanese SMEs (350 SMEs). Unlike other counterpart countries, such as South Korea, Japanese SMEs have been relatively slow in implementing Internet technologies into business practice. However, the results indicate that if Japanese SMEs allocate appropriate resources and deploy Internet capabilities these firms will benefit with performance gains. Further, we find that both the perception of risk-taking and the industry in which the firm operates are key factors in either inhibiting or enhancing the firm's ability to leverage Internet-related capabilities for firm performance.